The influence of AI adoption in customer service and its impact on customer satisfaction levels among Generation Z - Ong, Xin Chian; Tan, Qian Ying (2025)
Adoption of AI chatbot in customer service has become normalized in various industry to enhance business interactions with customers for better efficiency. The customer satisfaction on using AI chatbot has become a crucial issue and challenge to achieve at business level. This research is conducted to find out the linkage of the factors of AI chatbot service quality towards customer satisfaction among Generation Z. A total of 5 independent variables are proposed, including reliability (RL), responsiveness (RE), tangibles (TA), and empathy (EM), to study their effects on customer satisfaction (CS), the dependent variable of the research. And so, the study collected responses of 384 respondents with ages ranging from 13 to 28 years old, typically those in Malaysia, who experienced in AI customer service; after the pilot study, a small scale study of 30 respondents are done. With the data collected, the study utilized Software Package for Social Science (SPSS) to analyse the relationship between the DV and IVs in terms of reliability, coefficients and multiple regression. As a result, EM is found out to be having the greatest impact on CS, following by RL and TA, while AS and RE did not effect on the DV in our study. In addition, this study contributes to the future implications for both academicians and practitioners by offering significant insights to the modification of future research and guidance on designing AI chatbot for a better satisfaction from the customer and user perspective. Keywords: Customer Service, Artificial Intelligence, Generation Z, Customer Satisfaction, AI Chatbot Subject Area: HF5001-6182 Business